Safety and efficacy of esophageal stents for esophageal anastomotic strictures: A 10-year single-center experience - Sundus Bilal; Saad Muhammad Saeed; Zeeshan Siddique; Muhammad Saqib; Shahana Shahid; Muhammed Aasim Yusuf (Society of Gastrointestinal Intervention, 2022)
Background : : The aim of this study was to determine whether esophageal stent placement in recurrent and refractory post-esophagectomy anastomotic strictures improves clinical outcomes and prolongs the intervals between re-interventions. Methods : : This retrospective, observational, single-center study analyzed data from all patients who underwent esophageal stent placement for symptomatic benign post-esophagectomy anastomotic strictures from 2009 to 2019. The primary outcome was technical and clinical success. The secondary outcomes were stent-related complications and re-intervention duration and rates. Results : : Twenty-eight patients underwent esophageal stent placement for post-esophagectomy benign anastomotic strictures. The technical success rate was 96.4%. The clinical success rates at 4 weeks, 12 weeks, and 1 year were 100%, 69.23%, and 72.72%, respectively. Serious stent-related complications occurred in two patients (7.1%), while minor adverse events were noted in 11 patients (39.28%). The rate of stricture recurrence with a mean dysphagia-free interval of 17 weeks after stent placement was 64.28%. The rate of luminal patency with a stent was 73.33% at 12 months. Conclusion : : Stent insertion is an effective and safe treatment modality for anastomotic esophageal strictures. Long-term remission of the stricture, more luminal patency, and an improved dysphagia score were observed, but the findings need to be confirmed through multivariate analysis.